The Effect of Aloe Vera Extract on Wound Healing In Post Hospitalization Diabetes Mellitus Patients - Olviani, Yurida; Apriyanti, Uni; Hadrianti, Dessy; Saherna, Jenny; Hermawan, Aditya (Jurnal EduHealth, 2024)
The number of people with diabetes increases from year to year, accompanied by an increase in complications of diabetic ulcers. Various kinds of interventions are carried out to accelerate the healing of diabetic foot wounds, one of which is the use of aloe vera extract. To determine the effect of aloe vera extract on wound healing in patients with post-hospitalization diabetes mellitus. This study used a Pre-Experiment research design with a group Pretest post-test design. The population was all patients with diabetes mellitus and diabetic ulcers, and the sample was taken using the accidental sampling technique, totalling 37 people. Data analysis using the Wilcoxon Sign Rank Test Most of the wound healing before being given aloe vera extract was quite good. Namely, 26 people, or 70.3%, most wound healing after being given aloe vera extract was good; 28 people or 75.7%, there was an effect of providing aloe vera extract to wound healing in Diabetes Mellitus patients with a value of p = 0.000. Nurses should apply wound care using aloe vera as a non-pharmacological independent nursing action.